2012
DOI: 10.4149/neo_2012_027
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of potassium channel ether à go-go in human osteosarcoma

et al.

Abstract: Human ether à go-go (hEAG) potassium channels are primarily expressed in brain but also frequently overexpressed in solid tumors, which could indicate their potential value for cancer diagnosis and therapy. hEAG1, one member of the hEAG subfamily, has been shown to play a role in neoplastic process. Here we report the expression of hEAG1 in human osteosarcoma detected by a new polyclonal antibody. The full-length hEAG1 cDNA was cloned from human osteosarcoma cell line MG63 by RT-PCR and expressed in Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Since miRNAs have been largely reported to regulate gene expression, investigating the function of circRNAs will enable us to better understand the mechanisms underlying the occurrence and development of the associated diseases. Based on the findings in previous studies that potassium voltage-gated channel subfamily H member 1 (KCNH1) was overexpressed in osteosarcoma and promoted the proliferation and invasion of osteosarcoma [1113] and on our profile of the miRanda, PITA, RNAhybrid databases to explore the corresponding circRNAs of KCNH1, we speculated that hsa-circ-0016347 may be a potential regulator of osteosarcoma progression.…”
Section: Introductionmentioning
confidence: 99%
“…Since miRNAs have been largely reported to regulate gene expression, investigating the function of circRNAs will enable us to better understand the mechanisms underlying the occurrence and development of the associated diseases. Based on the findings in previous studies that potassium voltage-gated channel subfamily H member 1 (KCNH1) was overexpressed in osteosarcoma and promoted the proliferation and invasion of osteosarcoma [1113] and on our profile of the miRanda, PITA, RNAhybrid databases to explore the corresponding circRNAs of KCNH1, we speculated that hsa-circ-0016347 may be a potential regulator of osteosarcoma progression.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Eag1 (Kv10.1, KCNH1) channel attracts much interest due to its close relation to tumor growth, progression and metastasis. Eag1 is a central nervous system (CNS)-localized channel that is overexpressed in several tumor cell lines and more than 75% of primary solid tumors 22-24. The suppression of Eag1 expression caused a significant reduction of cancer cell proliferation 25-27.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly competitive for space and characterized by the ability to emit poison using structures of "aggression" called acrorhagi [34]. The voltage-gated potassium channel human ether-à-go-go 1 (hEag1, KV10.1), undetectable in normal tissues except for central nervous tissue, is widely overexpressed in different human tumor cyto-and histotypes, thereby being considered as a potential target for anticancer treatment [35,36]. In search of novel KV10.1 inhibitors, Moreels et al [37] reported the isolation of the peptide APETx4 (GTTCYCGKYIGIYWFGKYSCPTNRGYTGSCPYFLGICCYPVD) from A. elegantissima, which is able to bind to closed KV10.1 channels through its YFL hydrophobic patch and the charged residues present on one side and reduce their activation rate.…”
Section: Cnidaria-antozoamentioning
confidence: 99%